PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SMP SWASTA KOTA BOGOR - Dian Pintaningdyah (Jurnal Manajemen Pendidikan, 2017)
The objective of this research was to research and study the influence of Organization Culture and Job Satisfication toward Organizational Citizenship Behavior (OCB) of private high school teachers in Bogor City. The research was quatitative research with survey method that was analyzed using path analysis. Population target of the research was 200 private high school teachers in Bogor City, West Java Propince. Sampling technique using Random Sampling, that was taking sampling with simple random. Measured the amount of sampling used Slovin formula and the result was 133 respondent. The research shows that the coefficient path value of Organization Culture toward OCB 0,378with tstat of 0,303. Therefore, Organization Culture was directly influence toward OCB.The coefficient path value of Job Satisfication toward OCB 0,361 with tstat 0,280 .Therefore, Job Satisfication was directly influence toward OCB. The coefficient path value of Organizational Culture toward Job satisfication 0,267 with tstat 0,267 .Therefore, Organizational Culture was directly influence toward Job Satisfication.